Blue-green and red photoluminescence in CaTiO3 : Sm - de Figueiredo, Alberthmeiry T.; Longo, Valeria M.; de Lazaro, Sergio; Mastelaro, Valmor R.; De Vicente, Fabio S.; Hernandes, Antonio C.; Li, Maximo Siu; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Elsevier B.V., 2007)
Blue-green and red photoluminescence (PL) emission in structurally disordered CaTiO3:Sm (CT:Sm) powders was observed at room temperature with laser excitation at 350.7 nm. The perovskite-like titanate CT:Sm powders prepared by a soft chemical processing at different temperatures of annealing were structurally characterized by X-ray diffraction (XRD) and X-ray absorption near-edge structure (XANES). The results indicate that the generation of the broad PL band is related to order-disorder degree in the perovskitelike structure. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: luminescence; order-disorder; optical materials; CT : Sm